2020
DOI: 10.3803/enm.2020.719
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Glucose Level Independently Predicts the Mortality of Patients with Coronavirus Disease 2019 Infection: A Multicenter, Retrospective Cohort Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) has become a global pandemic, which prompts a consensus for the necessity to seek risk factors for this critical disease. Risk factors affecting mortality of the disease remain elusive. Diabetes and hyperglycemia are known to negatively affect a host's antiviral immunity. We evaluated the relationship between a history of diabetes, fasting plasma glucose (FPG) levels and mortality among severely ill patients with COVID-19. Methods: This was a retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Furthermore, we discovered that the smallersized studies yielded excessively wide CIs as compared to larger studies (Table 1). Nonetheless, sensitivity analysis suggested that these small studies did not contribute much to the pooled estimate as our findings remained consistent, except when Fadini et al [36] or Chang et al [38] were excluded, which exaggerated the pooled estimates (Appendix Figure S2B). We detected asymmetry in the funnel plot which was further ascertained by Egger's test (P<0.001; Appendix Figure S3), although Begg's test indicated otherwise (P=0.245), suggesting the presence of publication bias.…”
Section: Fasting Blood Glucosementioning
confidence: 51%
See 1 more Smart Citation
“…Furthermore, we discovered that the smallersized studies yielded excessively wide CIs as compared to larger studies (Table 1). Nonetheless, sensitivity analysis suggested that these small studies did not contribute much to the pooled estimate as our findings remained consistent, except when Fadini et al [36] or Chang et al [38] were excluded, which exaggerated the pooled estimates (Appendix Figure S2B). We detected asymmetry in the funnel plot which was further ascertained by Egger's test (P<0.001; Appendix Figure S3), although Begg's test indicated otherwise (P=0.245), suggesting the presence of publication bias.…”
Section: Fasting Blood Glucosementioning
confidence: 51%
“…Although our findings also favored the use of admission RBG, future research are required as we were unable to comprehensively explore the independent prognostic value of admission RBG due to paucity of studies. Furthermore, the current evidence indicated that the cut-off values to predict poor prognosis in COVID-19 patients are still equivocal [38,41,52,53], suggesting that future large multicenter studies are required to obtain the most optimum cut-off value.…”
Section: Discussionmentioning
confidence: 98%
“…To date, several studies have reported risk factors for COVID-19's progression, such as age, hypertension, use of angiotensin-converting enzyme inhibitors, and neurological disorders [8,[10][11][12][13]. For example, young individuals infected with SARS-CoV-2 generally show milder respiratory symptoms than older adults [13].…”
Section: Introductionmentioning
confidence: 99%
“…From 35 included studies, more than half were conducted in China (23 studies), while the others were five each in America 18,21,[27][28][29] and Europe 20,25,[30][31][32] , and one each in Hong Kong 33 and South Korea 34 . FBG was utilized in 23 studies, while RBG in 13 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%